STRONGLY PARACOMPACT MAPPINGS - Arar, Murad; Hdeib, Hasan (Italian Journal of Pure and Applied Mathematics, 2013)
In this paper, we define and study strongly paracompact mappings which are the fibrewise topological analogues of strongly paracompact spaces. Several characterizations and properties of strongly paractompact mappings are obtained.